Devaluation and its Effects on Turkish Trade Regime - AKALPLER, Ergin (Journal of Advanced Research in Law and Economics; Vol 7 No 2 (2016): JARLE, Volume VII, Issue 2(16), Spring 2016, 2016)
In this study devaluation and its effects on the Turkish trade regime between 1985 and 2014 is considered. Theoretical and practical experiences show that inflation and lower exchange rates can be used as an important instrument for increasing export capacity. In general, enlargement of export and devaluation of currency has significant positive impact on growth and development if domestic inputs are used in the production operation process. However, in Turkey devaluation is considered as an instrument for enlargement of export and development. Although in this regime, foreign inputs are used intensively for producing exportable goods, which is negatively affecting and reducing the impact of devaluation on the Turkish trade regime. After applying the Ordinary Least Square and Unit Root of which Augmented Dickey Fuller tests for the long period of time effects on selected variables, relationship between the inflation and export had no significant positive impact on trade capacity development. Similarly, when we consider the inflation rates for unit root test, its critical values for ADF test is becoming higher, which means devaluation of Turkish lira had a very small contribution on exportable goods as R squared values in OLS tests show 0.177 which is very low and inflation effects on growth rate is not significant.